Correction: Regulation of the DNA Damage Response and Gene Expression by the Dot1L Histone Methyltransferase and the 53Bp1 Tumour Suppressor. - Jennifer FitzGerald; Sylvie Moureau; Paul Drogaris; Enda O'Connell; Nebiyu Abshiru; Alain Verreault; Pierre Thibault; Muriel Grenon; Noel F Lowndes (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0014714.].